Nayanmars in Sivakami Sabatham - B, Vishnupriya (International Research Journal of Tamil, 2022)
Periyapuranam composed by Sekizhar is considered to be the tenth of the twelve Thirumurai. This book which dates back to the 12th century A.D is a Saivite scripture. This book has been greatly appreciated by the scholars of the West. It describes about the life of the people who showed concern over the worldly creatures and had worshipped God with love. It details about the life stories of the 72 Shaiva Nayanars. Sekizhar named this book as Tiruthondapuranam.